2022
DOI: 10.15244/pjoes/152836
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Land and Water Conservation Practices Against Runoff and Erosion

Abstract: The Land converted in the form of road construction crossing protected forest areas has resulted in the loss of vegetation diversity and while surface flow and erosion are accelerated. This research aimed at determining the effectiveness of land and water conservation practices in controlling runoff and erosion. The research method adopted in this investigation uses a multislot divider measuring 10 m x 5 m with a slope of 25% on geogrid, geonet, and vegetation cover plots, where each plot comprises 3 pieces, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…Tropical rainforests are vulnerable to disturbances in complex ecosystem processes caused by interactions between natural abiotic elements and high biodiversity. Therefore, such ecosystems will continue to be under threat of deforestation as a result of human pressure, with deforestation and degradation of tropical rainforests increasing vulnerability via various damaging effects on billions of people, as well the loss of vegetation diversity and accelerated runoff and erosion (Brandon, 2014;Lewis et al, 2015;Miller and Spoolman, 2016;Turubanova et al, 2018;Naharuddin et al, 2023).…”
Section: Model 4: Reforestation/plantation Forest Pattern Rehabilitationmentioning
confidence: 99%
“…Tropical rainforests are vulnerable to disturbances in complex ecosystem processes caused by interactions between natural abiotic elements and high biodiversity. Therefore, such ecosystems will continue to be under threat of deforestation as a result of human pressure, with deforestation and degradation of tropical rainforests increasing vulnerability via various damaging effects on billions of people, as well the loss of vegetation diversity and accelerated runoff and erosion (Brandon, 2014;Lewis et al, 2015;Miller and Spoolman, 2016;Turubanova et al, 2018;Naharuddin et al, 2023).…”
Section: Model 4: Reforestation/plantation Forest Pattern Rehabilitationmentioning
confidence: 99%
“…Dalam diskusi saat penyuluhan, bahwa dengan pengolahan lahan dengan cara lama banyak peserta yang mengeluhkan produktivitas tanaman dan lahan yang diusahakan kurang maksimal, karena kurangnya pengetahuan dan keterampilan penggunaan aplikasi teknologi pembuatan teras dalam proses penanaman. Penggunaan lahan yang tidak sesuai kaidah konservasi tanah dan air cenderung meningkatkan laju erosi, oleh karena itu disarankan bahwa pola agroforestry dapat diaplikasikan dalam meminimalisir laju aliran permukaan dan erosi [11], [12].…”
Section: Gambar 3 Penyuluhan Dan Pelatihanunclassified
“…In areas with low vegetation coverage, loose soil, and high precipitation intensity, soil erosion is prone to occur, resulting in the destruction of the ecological environment on the slope and threatening water security [107,108]. Based on ecological engineering construction measures such as slope afforestation, dry land terrace construction, and silt dam construction, it can reduce soil and water loss on the slope and repair and improve the ecological environment [109,110]. Gao et al [111] found that terraces have a significant effect on sediment reduction.…”
Section: Water and Soil Conservationmentioning
confidence: 99%